2021
DOI: 10.1093/ckj/sfab023
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic era: is it time to promote home dialysis and peritoneal dialysis?

Abstract: The novel coronavirus, called SARS-CoV-2 has been declared a pandemic on March 2020, by the World Health Organization. Older individuals and patients with comorbid conditions such as hypertension, heart disease, diabetes, lung disease, chronic kidney disease (CKD), and immunologic diseases are at higher risk of contracting this severe infection. In particular, patients with advanced CKD constitute a vulnerable population and a challenge in the prevention and control of the disease. Home-based renal replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 44 publications
2
25
0
1
Order By: Relevance
“…For some patients, peritoneal dialysis was the preferred mode of dialysis because it allowed them to stay home and conduct telehealth appointments remotely, thus alleviating fears of transmission as compared with haemodialysis. This finding is consistent with studies examining access to dialysis services during the H1N1 pandemic in 2009 (citation required) 25 . Ultimately, given the postulated lower risk of transmission, peritoneal dialysis remains the endorsed and preferred dialysis modality for patients during the COVID‐19 pandemic, but efforts need to be made to ensure appropriate equipment and training is provided to all patients seeking the peritoneal dialysis option 25 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For some patients, peritoneal dialysis was the preferred mode of dialysis because it allowed them to stay home and conduct telehealth appointments remotely, thus alleviating fears of transmission as compared with haemodialysis. This finding is consistent with studies examining access to dialysis services during the H1N1 pandemic in 2009 (citation required) 25 . Ultimately, given the postulated lower risk of transmission, peritoneal dialysis remains the endorsed and preferred dialysis modality for patients during the COVID‐19 pandemic, but efforts need to be made to ensure appropriate equipment and training is provided to all patients seeking the peritoneal dialysis option 25 …”
Section: Discussionsupporting
confidence: 80%
“…25 Ultimately, given the postulated lower risk of transmission, peritoneal dialysis remains the endorsed and preferred dialysis modality for patients during the COVID-19 pandemic, but efforts need to be made to ensure appropriate equipment and training is provided to all patients seeking the peritoneal dialysis option. 25 The use of telehealth consultations has emerged as a means to manage patient loads and allow patients to avoid travelling to hospital tionizing the landscape for primary health care. 26,27 Furthermore, telemedicine has enabled patients to assume an active role in their own health care.…”
Section: Discussionmentioning
confidence: 99%
“…Since the COVID-19 pandemic began, preliminary data have shown that patients receiving PD have lower risk of infection for COVID-19 than those receiving in-center HD, 34 underscoring the need to provide the option of urgent start PD. During the pandemic, many medical centers have considered arteriovenous fistula/arteriovenous graft placement surgery as nonurgent, leading to delayed access creation.…”
Section: Discussionmentioning
confidence: 99%
“…Dialysis patients affected by COVID-19 are more severely ill and have a higher mortality rate [ 3 5 ]. Therefore, JSDT has recommended all patients on dialysis who are diagnosed as COVID-19, including those with mild disease, to be hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, by December 29, 2021, 1.73 million people were affected by COVID-19 with more than 18,000 deaths [ 2 ]. Dialysis patients are known to be at a risk for severe disease [ 3 ]. The prognosis of COVID-19 patients with chronic kidney disease is poor, especially in those undergoing hemodialysis, in whom the mortality rate ranges from 14% [ 4 ] up to 50% in severe COVID-19 cases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%